Mixed fermentation of soybean meal by protease and probiotics and its effects on the growth performance and immune response in broilers. Issue 1 (1st January 2019) - Cheng, Yeong-Hsiang; Hsiao, Felix Shih-Hsiang; Wen, Chiu-Ming; Wu, Chia-Ying; Dybus, Andrzej; Yu, Yu-Hsiang
ABSTRACT: Soybean meal (SBM) contains several anti-nutritional factors, which limit the use of soy protein. Exogenous enzyme supplementation and microbial fermentation can reduce anti-nutritional factors and increase the bioavailability of nutrients in SBM. In this study, we investigated the optimal parameters for the solid-state fermentation (SSF) of SBM by protease in combination with probiotics and evaluated its effect on the growth performance and immune response in broilers. Protease in combination with Bacillus subtilis significantly increased the degradation of soybean protein and soybean allergens in a dose-dependent manner during the SSF of soybean meal. Broilers fed 10% fermented SBM (FSBM), which was produced with protease and B. subtilis, consumed more daily feed on average during the entire feeding period than the SBM group did ( P < 0.05). Dietary supplementation with 10% FSBM attenuated IL-4 mRNA expression in the spleen and bursa of Fabricius of broilers ( P < 0.05). Furthermore, 10%-FSBM-fed broilers had significantly lower serum anti-soybean IgG levels than SBM-fed broilers ( P < 0.05). These results suggest that the supplementation of B. subtilis and protease during the SSF of SBM reduces anti-nutritional factors. Moreover, dietary supplementation of 10% FSBM could inhibit the allergic immune response in broilers.